Comparison of Imaging Softwares for Upper Airway Evaluation: Preliminary Study - Trento, Guilherme dos Santos [UNESP]; Moura, Lucas Borin [UNESP]; Spin-Neto, Rubens; Juergens, Philipp Christian; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Thieme Medical Publ Inc, 2018)
The interest about upper airway evaluation has increased lately. Therefore, many softwares have been developed aiming to improve and facilitate the analysis of airway volume. The objective of this study was to compare two different softwares packages, Mimics and Dolphin, in their accuracy and precision in upper airway space measurements. Preoperative cone beam computed tomography scans of nine nonsyndromic patients submitted to surgically assisted rapid maxillary expansion were included in this study. The imaging exams were converted to DICOM (digital imaging and communications in medicine) files and imported to the softwares. The mean volume for the Dolphin group (G1) was 10.791 cm(3) (SD = 4.269 cm(3)) and for the Mimics group (G2) was 10.553 cm(3) (SD = 4.564 cm(3)). There was no statistically significant difference between the two groups (p = 0.105).
Keywords: imaging software; CBCT; posterior airway